(untitled) (Journal of Computational Mathematics, 2001)
In this paper, a nonoverlapping domain decomposition method, which is based on the natural boundary reduction (cf. [4,13,15]), is developed to solve the boundary value problem in exterior three-dimensional domain of general shape. Convergence analyses both for the exterior spherical domain and the general exterior domain are made. Some numerical examples are also provided to illustrate the method.